MSI2 deficiency in ILC3s attenuates DSS-induced colitis by affecting the intestinal microbiota - Li, Nengneng; Xu, Shiquan; Zhang, Shuaishuai; Zhu, Qiang; Meng, Xiaole; An, Wenbin; Fu, Baoqing; Zhong, Mengya; Yang, Yan; Lin, Zeyang; Liu, Xueni; Xia, Junjie; et al. (Frontiers in Immunology, 2023)
The etiology and pathogenesis of inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn's disease (CD), are generally believed to be related to immune dysfunction and intestinal microbiota disorder. However, the exact mechanism is not yet fully understood. As a subgroup of the innate immune system, group 3 innate lymphoid cells (ILC3s) are widely distributed in the lamina propria of the intestinal mucosa. Many molecules participate in regulating the function of ILC3s. Musashi2 (MSI2) is a type of evolutionarily conserved RNA-binding protein that maintains the function of various tissue stem cells. The effect of MSI2 deletion in ILC3s on IBD has not been reported. To this end, mice with conditional MSI2 knockout in ILC3s were used to construct a DSS-induced acute colitis model and explore its effects on the pathogenesis of IBD and the species, quantity and function of the intestinal microbiota. MSI2 flox/flox mice (MSI2 fl/fl) and MSI2 flox/floxRorc Cre mice (MSI2 Rorc) were induced by DSS to establish the IBD model. MSI2 was knocked out in the ILC3s of MSI2 Rorc mice. The MSI2 Rorc mouse model exhibited reductions in body weight loss, the disease activity index, the colon shortening degree, the tissue histopathological score and immune cells in the peripheral blood compared to those of MSI2 fl/fl mice. The 16S rRNA sequencing results showed that the diversity of the intestinal microbiota in DSS-treated MSI2 Rorc mice changed, with the abundance of Firmicutes increasing and that of Bacteroidetes decreasing. The linear discriminant analysis effect size (LEfSe) approach revealed that Lactobacillaceae could be the key bacteria in the MSI2 Rorc mouse model during the improvement of colitis. Using PICRUST2 to predict the function of the intestinal microbiota, it was found that the functions of differential bacteria inferred by modeling were mainly enriched in infectious diseases, immune system and metabolic functions. MSI2 deficiency in ILC3s attenuated DSS-induced colonic inflammation in mice and affected intestinal microbiota diversity, composition, and function, with Lactobacillaceae possibly representing the key bacteria. This finding could contribute to our understanding of the pathogenesis of IBD and provide new insights for its clinical diagnosis and treatment.